Methoxypyrazine composition of Coccinellidae‐tainted Riesling and Pinot noir wine from Germany. (15th July 2014) - Kögel, Susanne; Botezatu, Andreea; Hoffmann, Christoph; Pickering, Gary
Abstract BACKGROUND Harmonia axyridis (multicolored Asian ladybeetle) and Coccinella septempunctata (seven‐spot ladybeetle) (Coccinellidae) are found in many wine regions in Europe and the Americas, where they are responsible for a pronounced wine fault known as 'ladybug taint' when incorporated with grapes during harvest operations. Methoxypyrazines have been proposed in the literature as the compounds responsible for the taint. This study sought to expand on this identification and also determine the effectiveness of heating Coccinellidae‐affected grape must prior to fermentation as a possible remedial intervention. Riesling and Pinot noir grapes were infested with H. axyridis or C. septempunctata at different densities and fermented to dryness. The Pinot noir was either must heated prior to fermentation or processed without heating (control). All wines were analyzed for 2‐isopropyl‐, 2‐sec‐butyl‐, 2‐isobutyl‐ and 2, 5‐dimethyl‐3‐methoxypyrazine using headspace solid phase microextraction/multidimensional gas chromatography/mass spectrometry. RESULTS Concentrations of 2‐isopropyl‐3‐methoxypyrazine increased with beetle density for both Coccinellidae species, while other methoxypyrazines showed inconsistent or no variation with infestations levels. Heating of Pinot noir grapes prior to fermentation resulted in a moderate decrease in all methoxypyrazines. CONCLUSION These results provide direction for more targeted treatments aimed at remediating musts/wines affected by Coccinellidae and indicate that winegrowers do not need to differentiate between H. axyridis and C. septempunctata when making action threshold decisions in the vineyard or winery. © 2014 Society of Chemical Industry